1992
DOI: 10.1111/j.1365-246x.1992.tb03470.x
|View full text |Cite
|
Sign up to set email alerts
|

Separation of scattering and intrinsic attenuation for the Kanto-Tokai region, Japan, using measurements ofS-wave energy versus hypocentral distance

Abstract: S U M M A R YDetermining the relative amount of attenuation caused by scattering and intrinsic absorption is important to the understanding of wave propagation and attenuation in the heterogeneous lithosphere. A recently developed model based on radiative transfer theory provides a method for quantifying the ratio of scattering loss to total attenuation, which is called seismic albedo. The basic assumption of this model is that the medium is composed of a uniform distribution of isotropic scatterers. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
208
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 310 publications
(211 citation statements)
references
References 22 publications
2
208
0
1
Order By: Relevance
“…We also demonstrated that we could estimate the scattering coefficients and the intrinsic absorption separately by using the different time windows in a manner slightly different from the multiple lapse time analysis [e.g., Fehler et al, 1992;Hoshiba, 1991]. The estimated isotropic scattering coefficient in the 8-16 Hz band for P-to-P scattering is 0.24 km −1 and those of S-to-S and P-to-S scattering are 3 and 2.8 times larger than that of P-to-P scattering.…”
Section: Estimation Of the Scattering Coefficientsmentioning
confidence: 99%
“…We also demonstrated that we could estimate the scattering coefficients and the intrinsic absorption separately by using the different time windows in a manner slightly different from the multiple lapse time analysis [e.g., Fehler et al, 1992;Hoshiba, 1991]. The estimated isotropic scattering coefficient in the 8-16 Hz band for P-to-P scattering is 0.24 km −1 and those of S-to-S and P-to-S scattering are 3 and 2.8 times larger than that of P-to-P scattering.…”
Section: Estimation Of the Scattering Coefficientsmentioning
confidence: 99%
“…Scattering certainly represents the principal mechanism of seismic coda generation, and numerous efforts have been made for developing scattering-based coda models (Aki, 1969;Aki and Chouet, 1975;Dainty and Toksöz, 1977;Aki, 1980;Roecker et al, 1982;Aki, 1991;Hoshiba et al, 1991;Zeng et al, 1991;Fehler et al, 1992;Hoshiba, 1993;Paasschens, 1997;Chouet, 2003;Carcolé and Ugalde, 2008). However, in the author's opinion, model-based approaches will unlikely reach the accuracy required for unambiguous inversion for the in situ Q, and even more so -of its frequency dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent Q c is conventionally inverted for the in situ elastic (scattering, Q s ) and anelastic (intrinsic, Q i ) quality factors, which are associated with the properties of velocity/density fluctuations and anelastic energy dissipation, respectively (e.g., Jin and Aki, 1986;Aki, 1991). This inversion is usually based on the single-scattering (Aki and Chouet, 1975) or multiple-scattering models (e.g., Dainty and Toksöz, 1977;Fehler et al, 1992). All of these models use a number of strong assumptions and simplifications, such as the uniform or smooth velocity background, perfectly-known geometrical spreading (GS), absence of free-surface effects and layered reflectivity, and isotropic and often uniformly-distributed scattering.…”
Section: Introductionmentioning
confidence: 99%
“…The main cause of this scatter is known to be the different radiation pattern of each earthquake (e.g. Fehler et al, 1992). The regional alteration of local structure has also been thought of as one of the causes of the observational scatter (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used approach to the separation into Q i -1 and Q s -1 is multiple lapse time window analysis (MLTWA), introduced almost simultaneously by Hoshiba et al (1991) and Fehler et al (1992). Based on the observations that the early portion of a seismogram is dominated by the direct S-wave whose amplitude is reduced by Q t -1 , whereas the S-coda is composed entirely by scattered S-waves whose amplitude is reduced by Q i , MLTWA simulates the integral of the observed energy from multiple earthquakes in three successive time windows.…”
Section: Introductionmentioning
confidence: 99%